Book Review: Frontiers of Citizenship. A Black and Indigenous History of Postcolonial Brazil, by Yuko Miki - Boza Villarreal, Alejandra (2021)
The book by historian Yuko Miki represents an outstanding effort to combine two academic fields that have developed independently and rarely communicate with each other: studies on indigenous groups and studies on African-descendend peoples. Her goal is to understand the shared stories and the sometimes divergent trajectories of indigenous and African-descended populations that inhabited a region the author calls the «Atlantic frontier», during the period of the Brazilian Empire (1822-1889). The study shows that this type of academic integration can advance our understanding of nineteenth-century history. It also constitutes an exceptional example of a regional history that makes important contributions to key historiography about Brazil.